2017
DOI: 10.1007/s12671-016-0672-z
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Competence in Mindfulness-Based Cognitive Therapy for Depression and Its Relation to Treatment Outcome

Abstract: As mindfulness-based cognitive therapy (MBCT) becomes an increasingly mainstream approach for recurrent depression, there is a growing need for practitioners who are able to teach MBCT. The requirements for being competent as a mindfulness-based teacher include personal meditation practice and at least a year of additional professional training. This study is the first to investigate the relationship between MBCT teacher competence and several key dimensions of MBCT treatment outcomes. Patients with recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 59 publications
6
35
2
Order By: Relevance
“…Therapist competence did not have a significant effect on reduction of psychological distress. This is in line with previous findings that did not show a relationship between therapist competence and treatment outcome in MBCT for recurrent depression (Huijbers et al, ). In addition, previous research in CBT also found little support for an association between competence and patient outcome (Branson et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Therapist competence did not have a significant effect on reduction of psychological distress. This is in line with previous findings that did not show a relationship between therapist competence and treatment outcome in MBCT for recurrent depression (Huijbers et al, ). In addition, previous research in CBT also found little support for an association between competence and patient outcome (Branson et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It also corresponds with a recent trial showing that competence in delivering MBCT (including conveying course themes, guiding practice, embodiment of mindfulness, and relational skills) was not associated with posttreatment changes in depressive symptoms or with relapse and recurrence rates (Huijbers et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The finding that lower adherence was not predictive of poorer outcome in CBT and MBCT is consistent with a meta‐analysis finding no significant mean weighted association between therapist adherence and outcome of psychological treatments (Webb et al, ). It also corresponds with a recent trial showing that competence in delivering MBCT (including conveying course themes, guiding practice, embodiment of mindfulness, and relational skills) was not associated with posttreatment changes in depressive symptoms or with relapse and recurrence rates (Huijbers et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Possibly, this lack of mindfulness increase is attributable to the delivery of mindfulness exercises by inexperienced therapists. However, first studies found that therapists’ mindfulness competence and experience are not significantly associated with patient outcomes (Huijbers et al, ). Nevertheless, these results are only preliminary.…”
Section: Discussionmentioning
confidence: 99%